Essays on fiscal policy and public debt - Diniz, André Sander (2017)
This thesis is composed of three essays related to fiscal policy and public debt. The first chapter analyses quantitatively the relevance of different fiscal policy responses to a debt restructuring episode, taking into account endogenous default costs associated to the financial accelerator mechanism. The second chapter presents an empirical exercise on the effects of fiscal consolidations for Latin American countries, with the study of the impact on output and some aggregate demand components, as well as an investigation of the relative importance of revenue or expenditure-based adjustments and possible non-linearities in the economy's response. The third chapter suggests a simple political economy model to rationalize the presence of political budget cycles for external debt and tests the empirical implications of the model in a panel of developed and emerging economies.